2018
DOI: 10.9734/ajarr/2018/v1i313059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Kinesio Taping Applications on Ankle Range in Children with Spastic Cerebral Palsy: A Comparative Study

Abstract: Background and Purpose: Spastic cerebral palsy is accompanied with an increase in calf muscles’ spasticity and a decrease in the ankle range of motion. The purpose of the study was to compare muscle inhibitory with functional corrective Kinesio taping applications on children with spastic cerebral palsy. Methods: Thirty two children with spastic cerebral palsy were selected from the outpatient clinic of the faculty of Physical Therapy Cairo University. Muscle inhibitory and functional corrective Kinesio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The primary outcomes were knee ROM (flexion and extension) and the level of functional abilities. Knee ROM was assessed with patients in a supine position using a digital goniometer (baseline Absolute Axis 0-185 Degrees Digital Goniometer©) and expressed in degrees, which is a reliable and valid method of evaluating joint ROM due to its high accuracy and eliminating the chance of errors by determining the "true" vertical or horizontal distance from a measurement's starting point [16].…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcomes were knee ROM (flexion and extension) and the level of functional abilities. Knee ROM was assessed with patients in a supine position using a digital goniometer (baseline Absolute Axis 0-185 Degrees Digital Goniometer©) and expressed in degrees, which is a reliable and valid method of evaluating joint ROM due to its high accuracy and eliminating the chance of errors by determining the "true" vertical or horizontal distance from a measurement's starting point [16].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies we already report the presence of skin allergic reaction after taping application, although all precautions, preparations, sensitivity test and even proper KT application was ensured [10][11]. Another observational study of sixty neurological cases revealed that KT can cause Kinesio tape can cause allergies [12].…”
Section: Discussionmentioning
confidence: 99%
“…-Digital 180 Degree Range, 9 inch Arms, 12-1027) which consists of the integral absolute vertical and horizontal levels, reads 0-185° degrees on liquid-crystal display screen, and has ability to freeze angle measurement; Goniometer exterior is powder-coated steel with inch/cm marks screened onto arms and powered by 9V battery. The absolute axis goniometer eliminates the need to manually score each measurement that decreases the errors [13].…”
Section: -Ankle Rom Assessment (Digital Goniometer)mentioning
confidence: 99%